Recours À L’avortement Provoqué Chez Les Femmes En Union Des Quartiers Précaires De Yopougon À Abidjan - Mohamed, Doumbia (European Scientific Journal, ESJ, 2016)
In Côte d’Ivoire, 15 % of maternal deaths are related to illegal abortions. Despite the known consequences, abortion practice is increasing more and more in a restrictive legislative context. Few formal studies and national statistics on the phenomenon exist, much less at the level of precarious slums of Abidjan. This article is a contribution to the understanding of abortion practice in the unprivileged urban context of Yopougon in Abidjan. It aims to analyze the logics and conditions of abortion in the precarious slums of Yopougon. A survey of a sample of 309 women aged 15 to 49 years, living in union in six precarious slums and, an investigation in three public health facilities and five private clinics and among traditional healers were conducted. Results indicate an overall prevalence of 11%. Women who aborted are generally young (85.3%), with no education (35.30%) or primary level of education (32.35%). Proportion of women who aborted increase with parity up to three children and decreases from the fourth child. The lack of financial resources (79.41%) and the fear and stigma (47.05%) are the main reasons of abortion. The majority of abortions took place in private clinics (58.82%).